Inulin suitable as reduced-kilojoule carrier for production of microencapsulated spray-dried green Cyclopia subternata (honeybush) extract. (January 2017) - Pauck, Claire; de Beer, Dalene; Aucamp, Marique; Liebenberg, Wilna; Stieger, Nicole; Human, Chantelle; Joubert, Elizabeth
Abstract: Retention of phenolic compounds during spray-drying of an anti-diabetic C. subternata extract and physicochemical characteristics of spray-dried powders (pure extract and extract-carrier mixtures) were evaluated. Extract-carrier mixtures contained three levels (250, 500 and 750 g/kg) of the microencapsulating agents, namely corn syrup solids, commonly used by the food industry, and inulin, a low-kilojoule alternative. The amorphous spray-dried powders ranged from nearly free-flowing to cohesive. Their moisture content and water activity fell within the range of their monolayer moisture values. The moisture sorption isotherm of the pure extract showed very little hysteresis, contrary to the mixtures containing carriers. Similar values for calculated and experimental heat flow, determined by isothermal microcalorimetry, indicated the carriers to be compatible with the extract, except when used in a mixture containing 750 g/kg corn syrup solids per total solids. Spray-drying had no detrimental effect on the individual phenolic content, in particular the heat labile mangiferin, isomangiferin and 3-β-d -glucopyranosyliriflophenone, and the total antioxidant capacity of the extract. Microencapsulation of C. subternata extract with inulin by spray-drying thus provides a stable low-kilojoule powder, suitable for formulation of single-serve beverage mixtures that can be used by diabetics. Highlights: Inulin is a suitable carrier for spray-dried honeybush extract. Pure extract is more thermo-stable than when spray-dried with inulin. Extract and inulin are compatible as determined using microcalorimetry. Phenolic content of the extract was not detrimentally affected by carrier. Stability of benzophenones during spray-drying is shown for the first time.